Major procedure-related complications in a real-world cohort of patients undergoing transvenous lead extraction. (19th May 2022) - Doring, M; Lucas, J; Bode, K; Nedios, S; Hilbert, S; Ebert, M; Moscoso Luduena, C; Hindricks, G; Richter, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Transvenous lead extraction (TLE) is the mainstay therapy for device-related infections. Though TLE procedures are associated with low complication and high success rates, risk factors for major procedure-related complications remain not well defined. Purpose: To evaluate the safety and efficacy of TLE in a large single centre cohort and to identify risk factors for major complications. Methods: All consecutive patients undergoing TLE in our department between May 2012 and December 2021 were included in a prospective registry. Our protocol for TLE followed a stepwise approach according to lead dwell time and estimated complexity of the procedure: use of simple traction ± locking stylet (LS) ± mechanical and/or powered sheaths ± snare technique via a femoral or jugular access. Patient characteristics, procedural data and complications were gathered and analysed. Logistic regression analysis was applied to identify risk factors for major procedure related complications. Results: A total of 2218 leads (25.7% ICD leads) were targeted for TLE in 1060 patients (67.7 ± 14.8 years; 74% male). The mean lead dwell time was 82 ± 62 months. The leading indication for TLE was cardiac device related infection (CDRI) in 695 patients (65.6%), 373 (35.2%) had systemic and 322 (30.4%) localized infection. Leads were extracted by simple traction in 30%, traction with LS in 3.7%, dilator sheaths with LS in 47.7%, and additional use of powered mechanical sheaths in 14.6%. The snare technique was used in 3.9%, with additional venous entry from femoral in 3.5% and jugular in 1.0% of all targeted leads. TLE was completely successful in 92.6%, partially successful with lead fragments <4cm in 4.2%, and failed in 3.1% of all patients, which translated to a clinical success rate of 96.9%. Twenty-nine patients (2.7%) experienced minor and 18 patients (1.7%) had major procedure-related complications (cardiac tamponade/perforation) including 2 intraprocedural deaths (0.2%). Presence of abandoned leads (HR 8.41, 95% CI 3.21–22.02; p<0.001), lead-years-per-patient (HR 1.063, 95% CI 1.037–1.090; p<0.001), dwelling time of the oldest lead (HR 1.011, 95% CI 1.006–1.016; p<0.001), and a right-sided implantation (HR 2.68, 95% CI 1.05–6.83; p=0.04) were significant predictors of major complications in logistic regression analysis. Conclusion: TLE is feasible, effective and safe in our large single centre experience. Overall complication and failure rates are low. Following our TLE protocol, the presence of abandoned leads, a right-sided implantation and dwelling time of the extracted leads were associated with major procedure-related complications.